Enhanced membrane bioreactor (MBR) operation by optimisation of bacterial population - Wu, Bing (2008)
This research program aimed to identify the conditions in a MBR that would help to reduce membrane fouling. An alternative objective was to identify specialized biomass which were membrane friendly under typical MBR operating conditions. Dynamic EPS characteristics in a MBR were studied under periodic and sequential changes of operating parameters. Then parallel MBR systems were operated for a long period to investigate the effect of different substrate loadings, substrate compositions and SRTs on EPS production, bacterial community structure and membrane fouling tendency. Further, membrane fouling mechanisms caused by EPS was investigated by comparing the contributions of dissolved solids and suspended solids to membrane fouling in MBRs. DGGE technique and bacterial isolation were employed to study the functions of the strains isolated from the MBR. Membrane fouling mechanism of pure culture was analyzed by studying cell characteristics.